GrowING The Business - ING Has Embarked On A Three Year Plan To Transform Itself - The Star, Cecilia Kok (2008)
DR Nirmala Menon gets asked very often about how it feels to be the "woman on top" since taking the helm as CEO president of ING Insurance Bhd about a year ago. And she always replies that its a good feeling.